If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(-4-x)=2x+7
We move all terms to the left:
-3(-4-x)-(2x+7)=0
We add all the numbers together, and all the variables
-3(-1x-4)-(2x+7)=0
We multiply parentheses
3x-(2x+7)+12=0
We get rid of parentheses
3x-2x-7+12=0
We add all the numbers together, and all the variables
x+5=0
We move all terms containing x to the left, all other terms to the right
x=-5
| 126=7(x-5) | | 4x-5=2(2x+)= | | 19d+4d-14d=18 | | (5x+2)=(3x+12) | | 126=7(x-5 | | 34x-14x+14=3 | | 25^x-2=5^3x | | 10-5x+3x=-x | | -4r+2=8-8r | | 1/3x+2=-1/4x-5 | | 3(2x+6)=-46+40 | | r-20=-13 | | 1-2(x+18)=4(2x-6)-9x | | -15+5x=-4x+14 | | 0.24=0.26b-0.36 | | 1=n/5+4 | | -5×7k=-19 | | 2(x-3)+5=3(x-2)+8 | | 3/4x+5=1/5x−21/20 | | 5+x-11=4+6x | | 2/3y-1/2=5/6 | | 3x+2+2x+5=6x+2 | | -1x=+4 | | 76=p+9 | | 2(x-3)+6=3(x-2)+5 | | X=56+y | | 14j=-3 | | 3(2x-1)=15x+2-6 | | 71-5x=35+2x | | 3/4x-16=2x-6+4 | | 2(x-3)+5=3(x-2)+6 | | 0,5(x+3)=x+x |